1997
DOI: 10.1023/a:1007947329496
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In the course of screening for immunomodulators, we found a significant blastogenic activity specific for splenic B cells in the extracts of safflower (Carthamus tinctorius L.). Active fractions termed SF1 and SF2 were purified from dried petals of safflower by boiling water extraction, ethanol precipitation and Sepharose CL-2B column chromatography. The elution profiles of the gel filtration indicated that the molecular weight of SF1 and SF2 was estimated to be more than 100 kD. Major components of SF1 and SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In the study, a Carthamus tinctorius (CT) treated DC vaccine also stimulated splenic T lymphocytes to secrete IFN-g and IL-10, and heightened expressions of CD86, MHC-1, and MHC-II antigen-presenting cells. Studies have further demonstrated the antitumor effects of CT polysaccharides (Wakabayashi et al, 1997;Ando et al, 2002;Shi et al, 2010).…”
Section: Huoxue Tongluo (Formulas and Herbs That Promote Blood Circulmentioning
confidence: 99%
“…In the study, a Carthamus tinctorius (CT) treated DC vaccine also stimulated splenic T lymphocytes to secrete IFN-g and IL-10, and heightened expressions of CD86, MHC-1, and MHC-II antigen-presenting cells. Studies have further demonstrated the antitumor effects of CT polysaccharides (Wakabayashi et al, 1997;Ando et al, 2002;Shi et al, 2010).…”
Section: Huoxue Tongluo (Formulas and Herbs That Promote Blood Circulmentioning
confidence: 99%
“…Carthamus tinctorius L (safflower), which belongs to the Compositae family, has long been used in Chinese medicine in clinical settings for the treatment of various diseases due to its antioxidant properties. The chemical constituents in safflower have been reported to include lignans, flavonoids, triterpene alcohols and polysaccharides ( 9 12 ). Previous research has indicated that the main effective constituent of safflower is safflower yellow (SY), which is a flavonoid.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, developing methods for the preparation of purified SPS and PBPC as well as systematic studies of their structures are necessary. Although the extraction, purification, structure and biological activities of SPS and PBPC have been studied for decades, and some studies have elucidated their main constituent monosaccharide and typical glycosidic linkages (Wakabayashi et al, 1997;Zou, 2011;Yao et al, 2018;Hu, 2020), there is no systematic review analyzing both SPS and PBPC. There is also a lack of research on the structure-bioactivity relationships.…”
Section: Introductionmentioning
confidence: 99%